Somatosensory change detection in the aging brain - Strömmer, Juho (2011)
The study examined the brain’s automatic somatosensory change detection mechanism using event-related potentials (ERPs) to tactile electrical pulses to fingers in an oddball paradigm. Also the effects of aging to these ERPs were investigated comparing the data of young adults (N = 20, 22–27 years) with the data of aged participants (N = 12, 67–95 years). In the experiment, the participants were instructed to ignore finger stimuli and to be fully involved to a radio play during the electroencephalogram (EEG) recording. The electrical stimulation was delivered to participant’s forefinger and little finger in randomized order of standard (P = 0.85) and deviant (P = 0.15) stimuli. The analyzed components were P50 peak (30–80 ms), N80 peak (40–110 ms) and a positive deflection at the latency range of 150–200 ms (the mismatch response, MMR). The results revealed significantly different responses to standards than those to deviants in the young group, indicating the automatic detection of deviant stimuli analogically to mismatch negativity in the auditory and visual modalities. As hypotesized, the MMR was completely attenuated in the aged group. P50 and N80, instead, had prolonged latency in the aged group compared to young adults. The findings suggest that the somatosensory MMR is a good measure of change detection mechanism and age-related changes in it.